Biocompatibility of Portland Cement Modified with Titanium Oxide and Calcium Chloride in a Rat Model - Hoshyari, Narjes; Labbaf, Hossein; Jalayer Naderi, Nooshin; Kazemi, Ali; Bastami, Farshid; Koopaei, Maryam (Iranian Endodontic Journal, 2016)
Introduction: The aim of the present study was to evaluate the biocompatibility of two modified formulations of Portland cement (PC) mixed with either titanium oxide or both titanium oxide and calcium chloride. Methods and Materials: Polyethylene tubes were filled with modified PCs or Angelus MTA as the control; the tubes were then implanted in 28 Wistar rats subcutaneously. One tube was left empty as a negative control in each rat. Histologic samples were taken after 7, 15, 30 and 60 days. Sections were assessed histologically for inflammatory responses and presence of fibrous capsule and granulation tissue formation. Data were analyzed using the Fisher’s exact and Kruskal-Wallis tests. Result: PC mixed with titanium oxide showed the highest mean scores of inflammation compared with others. There was no statistically significant difference in the mean inflammatory grades between all groups in each of the understudy time intervals. Conclusion: The results showed favorable biocompatibility of these modified PC mixed with calcium chloride and titanium oxide. Keywords: Biocompatibility; Mineral Trioxide Aggregate; Portland Cement